2018
DOI: 10.1021/acs.iecr.8b03879
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Oxidation Degree of Graphene Oxides on their Adsorption, Flocculation, and Antibacterial Behavior

Abstract: The effect of the oxidation degree of two graphene oxides (GOs) on the adsorption of cationic methylene blue (MB) and anionic methyl orange (MO) dyes and on the coagulation of cationic goethite and anionic kaolin minerals was studied with respect to water treatment in the textile and mining industries. To this purpose, two GOs with high (GO-H) and low (GO-L) oxidation degrees were synthesized by the Hummer method and characterized by Fourier transform infrared spectroscopy, X-ray diffraction, and zeta potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Our preliminary experimental results indicated that higher total oxygen content (CTO) in CGOs was associated with higher loading capacities of CGOs for CMlrA ( Table S2 ). Thus, their different immobilization performances could be related to their degree of oxidation ( Tan et al., 2017 ; Zolezzi et al., 2018 ). To systematically explore the degree of oxidation on the immobilization performance of GO for MlrAs, nine types of HGOs (HGO 1 -HGO 9 ) were prepared using HGO 0 as raw material and by altering the amount of added KMnO4 oxidant and the method of synthesis (M1 or M2) ( Hummers and Offeman, 1958 ; Marcano et al., 2010 ) ( Figures 1 A and S2 ; Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our preliminary experimental results indicated that higher total oxygen content (CTO) in CGOs was associated with higher loading capacities of CGOs for CMlrA ( Table S2 ). Thus, their different immobilization performances could be related to their degree of oxidation ( Tan et al., 2017 ; Zolezzi et al., 2018 ). To systematically explore the degree of oxidation on the immobilization performance of GO for MlrAs, nine types of HGOs (HGO 1 -HGO 9 ) were prepared using HGO 0 as raw material and by altering the amount of added KMnO4 oxidant and the method of synthesis (M1 or M2) ( Hummers and Offeman, 1958 ; Marcano et al., 2010 ) ( Figures 1 A and S2 ; Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In solutions with pH values ranging from 5.3 to 9.3, HGO 5 zeta potentials were lower than those of HGO 0 , indicating that a high degree of oxidation in HGO 5 led to greater stability than HGO 0 over a wider pH range ( Table S6 ). The stabilities of HGOs in aqueous solutions can be attributed to the concentration of oxygenated functional groups and the dissociation of acid functional groups such as carboxylic acid (-COO - + H + ) and hydroxyl (OH − ) groups ( Reynosa-Martínez et al., 2020 ; Zolezzi et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…That oscillating ion cloud produced an alternating voltage at the two electrodes, the streaming potential, which is proportional to the zeta potential of the particles. This zeta potential technique implemented in the Stabino has been used recently and successfully in various applications of interest in mineral processing [24][25][26][27]. The solution pH was adjusted with analytical grade KOH, NaOH, LiOH, and CsOH, at a concentration of 0.5 M (Merck) and HCl 0.020 M (Merck), the latter in order to not introduce a base other than Cl − ; this disparity in concentration is to achieve an alkaline pH without using too much base and to have a slow and controlled evolution of the zeta potential to the acid pH.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it has been shown that the changes in the adsorption capacity and selectivity are strictly correlated with the chemical functionalization GO surface 37,38,[40][41][42][43] and degree of oxidation of graphene oxide. 44,45 Unfortunately, there are still some limitations that, if solved, can make utilization of GO-based materials in the wastewater-derived adsorption processes a widely applied methodology. In particular, these materials are typically highly dispersible in water, therefore their regeneration and repeated utilization are not economically feasible.…”
Section: Introductionmentioning
confidence: 99%